2000
DOI: 10.1024//1421-0185.59.4.221
|View full text |Cite
|
Sign up to set email alerts
|

The transition into work - An editorial commentary

Abstract: Different research perspectives on the transition into work are presented, and some trends and shortcomings are discussed. It is argued that an orientation toward transition as a crisis no longer seems appropriate for research. Rather, various contextual schemes embedding different courses of transition and the “gradualness” in a context of life-long learning actually characterise this period. The six articles of the special issue are commented upon with regard to the study of the transition into work domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
2
Order By: Relevance
“…In contrast to university entry and leaving the parental home, work entry was not associated with general time trends. These findings are in line with studies showing that the transition from school to work has a primarily neutral or positive impact on well-being (Arnold & Reicherts, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to university entry and leaving the parental home, work entry was not associated with general time trends. These findings are in line with studies showing that the transition from school to work has a primarily neutral or positive impact on well-being (Arnold & Reicherts, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…In sum, most studies found that work entry has neutral or positive effects on well-being. Based on some of these studies, Arnold and Reicherts (2000) argued that the school-to-work transition should not be considered a crisis. However, this argument draws on studies with designs which could only give a limited account of changes in well-being during the transition: For example, a study with only two measurement points (Elfering, Semmer, & Kälin, 2000; Kälin et al, 2000) and a short-term longitudinal study with frequent repeated measurements of the well-being of newcomers to a job several months after the transition (Reicherts & Pihet, 2000).…”
Section: Well-being During Normative Transitions In Young Adulthoodmentioning
confidence: 99%
“…Transition into work often is regarded as such a critical period (see Barling & Kelloway, 1999;Frese, 1982;Frone, 2000;Loughlin & Barling, 2001;Saks & Ashforth, 2000). This period seems to be associated with less disruption and more continuity than one might expect (Arnold, 1997;Arnold & Reicherts, 2000), and it may well imply positive developments (e.g., increasing job control and higher status; Ka ¨lin et al, 2000). Nevertheless, this transition still yields a good opportunity to capture early symptom development.…”
mentioning
confidence: 99%
“…La transition n'a pas, selon nous, pour finalité essentielle de produire ou de planifier, par phases successives et ordonnées, du changement, pas plus qu'elle n'est par essence stressogène et synonyme de difficultés psychologiques pour l'individu. Par conséquent, nous rejoignons les conclusions récentes d 'Arnold et Reicherts (2000) : « L'approche de la transition comme crise ne semble plus appropriée pour la recherche » (nous traduisons). Dans leur éditorial d'un numéro de la revue Swiss Journal of Psychology consacré aux tran-sitions que constituent les situations d'entrée au travail, ces auteurs dégagent plusieurs points clés qui nous paraissent importants à relever ici.…”
Section: Le Paradigme Du « Cours De La Vie » : Une Approche Cyclique ...unclassified